Chemical risk: state of the art of chemical substances exposure assessment - Jose Carlos Mora-Barrantes; Karla Alfaro-Aguilar; Melany Murillo-Chaverri; Marielia Calderón-Quesada; Ana Julia González-Marín (Tecnología en Marcha)
Given the ability of chemical substances to generate possible adverse effects on people’s health, it is necessary to identify, collect and integrate all the information related to the dangers associated with these substances. Throughout the years, the definition of risk has had different interpretations, which has given rise to different alternatives for its evaluation and management. Currently, there are several equipment and tools used in chemical risk assessment. In the present study, a bibliographic review was carried out for different chemical scenarios where sixteen chemical risk assessment methodologies were analysed during the period 2003-2020 that correspond to both, qualitative and quantitative methods. In conclusion, the risk assessment methodologies have undergone changes over the years according to the needs and increasing complexity of the systems where they apply, artificial intelligence could also be a useful tool in chemical risk assessment.